Effectiveness of Physical Activity Combined with Medical Rehabilitation in Cervical HNP Patient Post Radiofrequency Ablation (RFA) Procedure: A Case Report - Zahra, Nabila Luthfiyyah; Ramadhani, Fikar (International Medical Journal Corp. Ltd, 2024)
Introduction : Cervical disc herniation most likely happens in people over 30-years-old-age with a job that need holding a posture that can make body alignment easily diverge. Case presentation : A 48-year-old male presented with radiate pain from the wrist going upward to the neck. He also felt numbness or tingling sensation on the right side of the arm. MRI showed protrusion of intervertebral disc C5-6 and C6-7 with narrowing of right and left neural foramen. The patient was diagnosed with C5-C6 cervical disc herniation, Radiofrequency Ablation (RFA) was performed twice. An Anterior Cervical Discectomy and Fusion (ACDF) procedure was suggested but the patient declined it and then he received 3 months of physical therapy, and he performed physical activity regularly. Eventually the patient reported resolution of all the symptoms after. Conclusions : This case report emphasizes the effectiveness of combining physical activity with medical rehabilitation in a patient with cervical herniated nucleus pulposus after RFA procedure. The combination of these approaches yielded positive results measured by NPRS and ROM examination, with the patient experiencing reduced pain, improved daily function, and return to their daily activities.